2021
DOI: 10.3390/aerospace8080214
|View full text |Cite
|
Sign up to set email alerts
|

Design and Structural Analyses of a Reciprocating S1223 High-Lift Wing for an RA-Driven VTOL UAV

Abstract: In the design stage of an aircraft, structural analyses are commonly employed to test the integrity of the aircraft components to demonstrate the capability of the structural elements to withstand what they are designed for, as well as predict potential failure of the components. This research focused on the structural design and analysis of a high-lift, low Reynolds number airfoil profile, the Selig S1223, under reciprocating inertial force loading, to determine the feasibility of its use in a new reciprocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Due to the drone carrying detectors for low altitude search, altitude within 5-20 m, flight speed range of 5-15 m/s, the initial chord length c is 80 mm, r is the airflow density as 1.225 kg/m 3 (Imumbhon et al, 2021). According to the preliminary selected data, according to the above formula ( 16), the maximum thrust of the designed propeller is 60.51 N. According to the maximum take-off weight of 30 kg, the overall lift generated by the coaxial rotor is estimated to be 363.06 N, about 37 kg, which meets the design requirements.…”
Section: Airfoil Designmentioning
confidence: 99%
“…Due to the drone carrying detectors for low altitude search, altitude within 5-20 m, flight speed range of 5-15 m/s, the initial chord length c is 80 mm, r is the airflow density as 1.225 kg/m 3 (Imumbhon et al, 2021). According to the preliminary selected data, according to the above formula ( 16), the maximum thrust of the designed propeller is 60.51 N. According to the maximum take-off weight of 30 kg, the overall lift generated by the coaxial rotor is estimated to be 363.06 N, about 37 kg, which meets the design requirements.…”
Section: Airfoil Designmentioning
confidence: 99%
“…Schematic illustration of the design and simulation procedure of this study. (Cao 2019;Imumbhon et al 2021). These values indicate the RA wing performance is superior to rotary wings but similar to fixed wings.…”
Section: Selig S1223 Airfoil Summarymentioning
confidence: 99%
“…The literature review on the RA wing revealed that the RA VTOL aircraft is at a very early developmental stage (Cao 2019;Cao 2020;Alam and Cao 2021;Imumbhon et al 2021). Nevertheless, RA-driven VTOL aircraft (Cao 2019;Cao 2020) may have the potential to overcome the many challenges discussed above.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have looked into using the S1223 for high-lift and relatively slow flight applications due to its relatively high maximum lift coefficient [7]. The S1223 airfoil has a high lift and a low Reynolds number, making it ideal for short-field aircraft operations.…”
Section: Literature Reviewmentioning
confidence: 99%